Case report of transcatheter aortic valve implantation to the patient with severe aortic stenosis, atrial fibrillation, endovascular occlusion of the left atrial appendage and Mallory-Weiss syndrome - M. K. Barkovskaya; Z. S. Valieva; D. I. Darensky; A. S. Tereschenko; T. V. Martynyuk (Евразийский Кардиологический Журнал)
The case of a 81-year-old male with atrial fibrillation, associated with severe aortic stenosis (AS) is outlined. A peculiarity of the clinical portrait of AS is a long asymptomatic period with a significantly varying duration. After the appearance of the first clinical manifestations of the disease (shortness of breath on exercise, fainting) the risk of sudden death rises sharply, and the average life expectancy is 2-3 years. The development of atrial fibrillation (AF) leads to a serious impairment of the clinical condition due to loss of the contribution of atrial systole to the filling of the left ventricle (LV). Concentric hypertrophy of the LV, which at the first stage is an important adaptation mechanism compensatingfor a high intracavitary pressure, later leads to a relative reduction of the coronary blood flow and to limitation of the coronary vasodilatation reserve. So patient was referred for transcatheter aortic valve implantation. He had also a history of coronary artery disease with earlier percutaneous coronary intervention. Then, he was started on a triple antithrombotic therapy therapy. The triple antithrombotic therapy caused gastrointestinal bleeding (Mallory-Weiss syndrome). Considering the difficulties in the rational choice of anticoagulant therapy and high risks of adverse reactions, the patient underwent endovascular occlusion of the left atrial appendage.